IGR J17544-2619: a new supergiant fast X-ray transient revealed by optical/infrared observations - Pellizza González, Leonardo Javier (2006)
One of the most recent discoveries of the INTEGRAL observatory is the existence of a previously unknown population of X-ray sources in the inner arms of the Galaxy. IGR J17544-2619, IGR J16465-4507 and XTE J1739-302 are among these sources. Although the nature of these systems is still unexplained, the investigations of the optical/NIR counterparts of the two last sources, combined with high energy data, have provided evidence of them being highly absorbed high mass X-ray binaries with blue supergiant secondaries and displaying fast X-ray transient behaviour. In this work we present our optical/NIR observations of IGR J17544-2619, aimed at identifying and characterizing its counterpart. We show that the source is a high mass X-ray binary at a distance of 2-4 kpc with a strongly absorbed O9Ib secondary, and discuss the nature of the system.